ANALISIS CAIRAN DARAH (TRANSUDAT) DAN SERUM CAMPURAN (EKSUDAT) DI PENDERITA DENGAN REMBESAN SELAPUT PARU (EFUSI PLEURA) - Didi Irwadi; Sulina Y. Wibawa; Hardjoeno Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Pleural effusion is a fluid excess into pleural cavity due to transudation or exudation processes. The fluid deposited in the cavity canthreat the patient’s life. The pleural effusion could be produced in a patient with tuberculosis, cancer, cardiac failure, renal failure orviral/bacterial infection. The study is aimed to analyze the patterns of substance in the pleural effusion fluids produced by differentdiseases. A cross sectional study was performed from June 2006 to June 2007 at Clinical Pathology Laboratory of Dr. WahidinSudirohusodo Hospital, Makassar. The fluids were tested for glucose, total protein, LDH, and leukocyte count. Of 87 pleural effusion fluidsamples from 14–80 years old patients, 34.5% were transudates and 65.5% were exudates. Glucose value was higher (one tail T test,p < 0.01) in transudates group, whereas protein, LDH and leukocyte count were higher (one tail T test, p < 0.01) in exudates group.There were no significant differences of glucose, protein, LDH and leukocyte count among diseases within transudates group, as well aswithin exudates group. Staphylococcus spp., Klebsiella spp., and Acinetobacter spp., were the predominant bacteria revealed from thefluid cultures. Values of glucose, protein, LDH and leukocyte count have a different pattern between transudates and exudates groups.However, no special patterns were found among diseases within groups.